Pengaruh Strategi Buzzer Dalam Amplifikasi Pesan Kepada Publik Pada Lingkungan Demokrasi Politik - Nurul Jannah Lailatul Fitria (Talenta Publisher, 2023)
Indonesia has been listed as a multifaceted Internet country. Even Indonesia ranks with a large number of Internet users in the world. People's use of the Internet and technology created communicators, such as infludilution and buzzer. The communicators represent digital marketing. The influence and the buzzer used social media to communicate information. Specifically, buzzer was not only the digital marketing of products and services but was transitively converted into political buzzers. It was based on this research to say the buzzer was the role of the casting of messages in a time of political democracy. Research USES descriptive qualitative methods by expounding a phenomenon in detail and the reality of a phenomenon with the results of data collection in the field. Collecting literature or literature data. To identify the buzzer, its message with the buzzer and buzzer in the maelstrom of political democracy. Some picture examples of amplifying the message by the buzzer led to negative democracy instead of positive democracy. There is amplification of messages that lead to false news, hate speech and black campaign. The conditions proved that the buzzer in the amplification of a democratic form of democracy went away mainly in the political sphere.